PEMANFAATAN CITRA DIGITAL LANDSAT 7 ETM+ DAN SISTEM INFORMASI GEOGRAFIS UNTUK KAJIAN SPASIAL ESTIMASI PRODUKSI PADI KABUPATEN SRAGEN, PROVINSI JAWA TENGAH - , Rahning Utomowati,S.Si; , Prof. Dr. Totok Gunawan M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Based on the importance of rice as a staple food most of the people of Indonesia, the volume of rice production every year should be controlled, through the estimation of production. Various methods have been developed to estimation production of rice, one of which by using a remote sensing method. The aims of the study are : (1). To determine a suitable the transformation of the vegetation index is used as the base for production estimation of rice, (2). To asses the ability of Landsat 7 ETM+ imagery in the extraction data of rice fields area to estimate the production of rice, and (3). To find our the spatial distribution of production estimation of rice in Sragen regency based on transformation of vegetation index of Landsat 7 ETM+ imagery and analysis of Geographic Information Systems (GIS). The main data source is Landsat 7 ETM+ imagery recorded on 30 August 2002, which is used for extraction rice fields data and production estimation of rice. Land cover maps and landforms maps wich derived from Landsat 7 ETM+ imagery is used as the basis for production estimation of rice. Transformation of vegetation index method used in this study is the transformation of NDVI and SAVI. Productivity of rice data derived from measurements field. The data analysis used the spatial descriptions using analysis of Geographic Information Systems(GIS). Results of this research show that : (1). Based on the results of correlation between the productivity of rice with the brightness value, the correlation coefficient (r) between variables SAVI with productivity is 0.841 and the value of r Â² = 0.707, while the value of the correlation coefficient (r) between variables NDVI with productivity is 0.844 and the value of r Â²= 0, 712, so between SAVI and NDVI variables with productivity variables have positive correlation and strong correlation. Thus, the transformation of NDVI and SAVI indices can be used as the basis for estimation production of rice in the research area. (2), Based on the interpretation of test matrices, obtained accuracy of image interpretation of Landsat 7 ETM + is 90.22%. Thus, the Landsat 7 ETM+ imagery have a high accuracy for the extraction of rice fields of data required for estimation production of rice. The accuracy of test results obtained at 89.063%, thus the Landsat ETM+ imagery have a high accuracy for the production estimation of rice, so an alternative method that can be used to estimate rice production. (3). Based on the results of the analysis of Landsat 7 ETM +, the estimated production of rice in Sragen regency of 125,110.11 tons for a single harvest, or amounting to 375.060,45 tons in 2002. The highest rice production found on alluvial plains with volcanic material landforms, on the foot slope landforms, and alluvial plains with sedimentary material landforms. Subdistrict Sidoharjo, Ngrampal, Sragen and Plupuh a district that has a substantial production of rice, while the district that has a relatively sma ll rice production is Subdistrict Jenar, Tangen, and Miri.